Astrophysical Origins for the Unusual Chemical Abundance of the Globular Cluster Palomar 1. (4th January 2016) - Niu, Ping; Cui, Wenyuan; Zhang, Bo; Xie, Geying
Abstract: Unusual elemental abundances in globular cluster Palomar 1 (Pal 1) could provide important information for us to study the relation between the globular cluster and our Galaxy. In this work, we study the abundances of α elements, Fe-peak elements, and neutron-capture elements in Pal 1. We found that the abundances of the SNe Ia and main s-process components of Pal 1 are larger than those of the disk stars and the abundances of the primary component of Pal 1 are smaller than those of the disk stars with similar metallicity. The Fe abundances of Pal 1 and the disk stars mainly originate from the SNe Ia and the primary component, respectively. Although the α abundances dominantly produced by the primary process for the disk stars and Pal 1, the contributions of the primary component to Pal 1 are smaller than the corresponding contributions to the disk stars. The Fe-peak elements V and Co mainly originate from the primary and secondary components for the disk stars and Pal 1, but the contributions of the massive stars to Pal 1 are lower than those of the massive stars to the disk stars. The Y abundances mainly originate from the weak r-component for the disk stars. However, the contributions of the main s-components and main r-components to Y are close to those of the weak r-component for Pal 1. The Ba abundances of Pal 1 and the disk stars mainly originate from the main s-component and the main r-component, respectively. Our calculated results imply that the unusual abundances of Pal could be explained by the top-light IMF for Pal 1's progenitor-system.